2007
DOI: 10.1007/s10457-007-9057-6
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of fallows on selected soil hydraulic properties in a kaolinitic soil subjected to conventional tillage (CT) and no tillage (NT)

Abstract: Improved fallows have been used to reduce time required for soil fertility regeneration after cropping in low input agricultural systems. In semi-arid areas of Southern Africa, Acacia angustissima and Sesbania sesban are among some of the more widely used improved fallow species. However the residual effects of improved fallows on soil hydraulic properties during the cropping phase is not known. The aim of this study was to quantify the residual effects of fallows and tillage imposed at fallow termination on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
3
20
0
1
Order By: Relevance
“…In improved fallows, legumes are planted on fallow land for 1 to 2 years to improve soil fertility. The other advantage of fallowing is that it also improves soil physical properties, such as infiltration rates, hydraulic conductivity, and soil porosity (Nyamadzawo et al, 2008a), besides reducing soil and nutrient losses through runoff (Nyamadzawo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In improved fallows, legumes are planted on fallow land for 1 to 2 years to improve soil fertility. The other advantage of fallowing is that it also improves soil physical properties, such as infiltration rates, hydraulic conductivity, and soil porosity (Nyamadzawo et al, 2008a), besides reducing soil and nutrient losses through runoff (Nyamadzawo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of improved fallowing and conservation tillage can further improve the soil hydraulic properties (Alegre and Rao, 1996;Norwood, 1994), soil water-holding capacity (Nyamadzawo et al, 2008a) and improve organic carbon stocks in soils (Nyamadzawo et al, 2008b). Improved fallows can play an important role in mitigating climate change through carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in soil structure under fertiliser trees was evident, as reflected by the results from time-to-runoff studies (Phiri et al, 2003). Rainfall simulation studies (Nyamadzawo et al, 2007) also indicated that sesbania and gliricidia mixed with Dolichos increased infiltration rates significantly compared with continuously fertilised maize plots.…”
Section: Improvement In Soil Physical Propertiesmentioning
confidence: 69%
“…2), soil penetration resistance (Fig. 3), and reduced runoff and soil losses (Nyamadzawo et al, 2007;Phiri et al, 2003). Treatments involving fertiliser trees (leucaena, gliricidia, sesbania) have consistently shown significantly higher infiltration rates than monoculture maize (Fig.…”
Section: Improvement In Soil Physical Propertiesmentioning
confidence: 99%
“…3(f) (Taylor et al, 1966;Kim et al, 2010). 그리고 대공극 은 토양침투와 직접적으로 관계가 있고 (Nyamadzawo et al, 2008;Wang et al, 1986) 경운에 의해서 토양특성이 바뀌기 때문에 (Elwell, 1992;Beare et al, 1994) …”
Section: 토양의 공극율 토양의 공극율은 경운형태와 퇴적물의unclassified